Population Dynamics, Winter Ecology and Social Organization of Coats Island Caribou - Gates, C.C.; Adamczewski, J.; Mulders, R. (ARCTIC, 1986)
The indigenous caribou population of Coats Island, N.W.T., suffered major declines from winter mortality in the winters of 1974-75 (a 71% loss) and 1979-80. There was a minor die-off in the winter of 1983-84. Apparently in the major declines the entire calf cohorts (1974 and 1979) died. In the less drastic decline in 1983-84 males, calves and adults, died at greater rates than females. The over-winter losses occurred at different densities and hence were density independent, resulting from snow accumulation and a sparse food supply. Reproductive success was low following severe winters, with 3.7% calves in June 1975 and 8.5% in June 1980. In other years, despite poor winter nutrition, the herd was productive: fall calf: cow ratios of 76:100 in 1981, 57:100 in 1982 and 102:100 in 1983. Apparently cows that survived winter starvation were able to recover despite a short growing season, in the absence of insect and predation influences, and to conceive the following autumn. High summer calf survival in the absence of predation, plus the high proportion of cows in the herd (83%), provided the means for rapid recovery in numbers (r=0.21) when winter conditions ameliorated sufficiently that starvation did not occur.Key words: island caribou, winter mortality, population regulation, social organization Mots clés: caribou des îles, mortalité hivernale, contrôle de la population, organisation sociale